# Definite Integral to Infinity of Hyperbolic Sine of a x over Exponential of b x minus One

## Theorem

$\ds \int_0^\infty \frac {\sinh a x} {e^{b x} - 1} \rd x = \frac 1 {2 a} - \frac \pi {2 b} \cot \frac {a \pi} b$

where:

$a$ and $b$ are positive real numbers with $b > a$
$\cot$ denotes the cotangent function.

## Proof

 $\ds \int_0^\infty \frac {\sinh a x} {e^{b x} - 1} \rd x$ $=$ $\ds \frac 1 2 \int_0^\infty \frac {e^{-b x} \paren {e^{a x} - e^{-a x} } } {1 - e^{-b x} }$ Definition of Hyperbolic Sine $\ds$ $=$ $\ds \frac 1 2 \int_0^\infty \paren {e^{\paren {a - b} x} - e^{-\paren {a + b} x} } \sum_{n \mathop = 0}^\infty e^{-n b x}$ Sum of Infinite Geometric Sequence $\ds$ $=$ $\ds \frac 1 2 \sum_{n \mathop = 0}^\infty \int_0^\infty \paren {e^{\paren {a - \paren {n + 1} b} x} - e^{-\paren {a + \paren {n + 1} b} x} } \rd x$ Fubini's Theorem $\ds$ $=$ $\ds \frac 1 2 \sum_{n \mathop = 0}^\infty \paren {\intlimits {\frac {e^{\paren {a - \paren {n + 1} b} x} } {a - \paren {n + 1} b} } 0 \infty - \intlimits {-\frac {e^{-\paren {a + \paren {n + 1} b} x} } {a + \paren {n + 1} b} } 0 \infty}$ Derivative of Exponential of a x

Note that as $b > a$, we have that $a - b < 0$.

As $b > 0$, we therefore have $a - \paren {n + 1} b < 0$ for all positive integer $n$.

We also have that as $a + \paren {n + 1} b > 0$, that $-\paren {a + \paren {n + 1} b} < 0$.

$\ds \lim_{x \mathop \to \infty} \frac {e^{\paren {a - \paren {n + 1} b} x} } {a - \paren {n + 1} b} = 0$

and:

$\ds \lim_{x \mathop \to \infty} \frac {e^{-\paren {a + \paren {n + 1} b} x} } {a + \paren {n + 1} b} = 0$

We therefore have:

 $\ds \frac 1 2 \sum_{n \mathop = 0}^\infty \paren {\intlimits {\frac {e^{\paren {a - \paren {n + 1} b} x} } {a - \paren {n + 1} b} } 0 \infty - \intlimits {-\frac {e^{-\paren {a + \paren {n + 1} b} x} } {a + \paren {n + 1} b} } 0 \infty}$ $=$ $\ds \frac 1 2 \sum_{n \mathop = 0}^\infty \paren {\frac 1 {\paren {n + 1} b - a} - \frac 1 {\paren {n + 1} b + a} }$ Exponential of Zero $\ds$ $=$ $\ds \sum_{n \mathop = 0}^\infty \frac a {\paren {n + 1}^2 b^2 - a^2}$ Difference of Two Squares $\ds$ $=$ $\ds -\frac 1 b \sum_{n \mathop = 1}^\infty \frac {\paren {\frac a b} } {\paren {\frac a b}^2 - n^2}$ shifting the index, extracting factors

By Mittag-Leffler Expansion for Cotangent Function, we have:

$\ds \pi \cot \pi z = \frac 1 z + 2 \sum_{n \mathop = 1}^\infty \frac z {z^2 - n^2}$

where $z$ is not an integer.

Setting $z = \dfrac a b$, we have:

$\ds \pi \cot \frac {\pi a} b = \frac b a + 2 \sum_{n \mathop = 1}^\infty \frac {\paren {\frac a b} } {\paren {\frac a b}^2 - n^2}$

Rearrangement gives:

$\ds \frac \pi 2 \cot \frac {\pi a} b - \frac b {2 a} = \sum_{n \mathop = 1}^\infty \frac {\paren {\frac a b} } {\paren {\frac a b}^2 - n^2}$

So:

 $\ds \int_0^\infty \frac {\sinh a x} {e^{b x} - 1} \rd x$ $=$ $\ds -\frac 1 b \sum_{n \mathop = 1}^\infty \frac {\paren {\frac a b} } {\paren {\frac a b}^2 - n^2}$ $\ds$ $=$ $\ds \frac 1 {2 a} - \frac \pi {2 b} \cot \frac {a \pi} b$

$\blacksquare$